The Male-Female Gap in Physician Earnings: Evidence from a Public Health Insurance System - Engelbert Theurl; Hannes Winner (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2010)
Empirical evidence from U.S. studies suggests that, on average, female physicians earn less than their male counterparts. This gap in earnings does not disappear when individual and market characteristics are con- trolled for. This paper investigates whether a gender earnings difference can also be observed in a health care system predominantly financed by public insurance companies. Using a unique data set of physicians' earn- ings recorded by a public social security agency in an Austrian province between 2000 and 2004, we find a gender gap in average earnings of about 32 percent. A substantial share of this gap (20 to 47 percent) cannot be explained by individual and market characteristics, leaving labor market discrimination as one possible explanation for the observed gender earn- ings difference of physicians.
Keywords: I11; I18; J31; J71; 330; Health care financing; physician earnings; wage composition